Envelope Recombination: A Major Driver in Shaping Retroviral Diversification and Evolution within the Host Genome - Saili Chabukswar; Nicole Grandi; Liang-Tzung Lin; Enzo Tramontano (Viruses, 2023)
Endogenous retroviruses (ERVs) are integrated into host DNA as the result of ancient germ line infections, primarily by extinct exogenous retroviruses. Thus, vertebrates’ genomes contain thousands of ERV copies, providing a “fossil” record for ancestral retroviral diversity and its evolution within the host genome. Like other retroviruses, the ERV proviral sequence consists of gag, pro, pol, and env genes flanked by long terminal repeats (LTRs). Particularly, the env gene encodes for the envelope proteins that initiate the infection process by binding to the host cellular receptor(s), causing membrane fusion. For this reason, a major element in understanding ERVs’ evolutionary trajectory is the characterization of env changes over time. Most of the studies dedicated to ERVs’ env have been aimed at finding an “actual” physiological or pathological function, while few of them have focused on how these genes were once acquired and modified within the host. Once acquired into the organism, genome ERVs undergo common cellular events, including recombination. Indeed, genome recombination plays a role in ERV evolutionary dynamics. Retroviral recombination events that might have been involved in env divergence include the acquisition of env genes from distantly related retroviruses, env swapping facilitating multiple cross-species transmission over millions of years, ectopic recombination between the homologous sequences present in different positions in the chromosomes, and template switching during transcriptional events. The occurrence of these recombinational events might have aided in shaping retroviral diversification and evolution until the present day. Hence, this review describes and discusses in detail the reported recombination events involving ERV env to provide the basis for further studies in the field.